D.O. control and O.U.R. estimation in the activated sludge process - Bocken, Stephan (Department of Chemical Engineering, 2016)
The objective of this investigation was to evaluate Holmberg's method for simultaneous dissolved oxygen control and parameter estimation in a completely mixed diffused air activated sludge reactor.